Expression and quantification of RORγt and interleukin-17 in intestinal mucosa of newborn alpaca (Vicugna pacos) - Murga A., Gustavo (2018)
The aim of the study was to determine the relative levels of expression of messenger RNAs of RORγt and IL-17 in intestinal mucosa of clinically healthy newborn alpacas. Three age groups were formed: 2 to 7 days (group 1, n=5), 8 to 20 days (group 2, n=6) and 26 to 47 days (group 3, n=6), regardless sex or breed. Samples were taken from the middle segment of the jejunum. The total RNA was extracted, and the RT-PCR technique was used with specific primers. The relative expression of mRNA of RORγt and IL-17 was determined by the 2-ΔΔCt method using two neonatal pups as calibrators and using GAPDH as an endogenous control. The kinetics of expression of RORγt showed a constant trend during the first and third week of life, reaching its maximum expression in animals from 2 to 7 days of age, unlike IL-17 whose expression was progressive with age, evidencing a high stimulation and expression from the first days of age.